Post-surge structural glaciology of the ice margin of Múlajökull, central Iceland, and composition and distribution of geometrical ridges in the forefield - Magnús Freyr Sigurkarlsson 1990- (2018)
This thesis deals with the structural glaciology of the ice margin of Múlajökull, a surge-type glacier in central Iceland, and the distribution and composition of till ridges that are exposed in the immediate foreland. Detailed structural mapping, glacial geological and geomorphological methods, drone and aerial images, photogrammetry and remote sensing are used to investigate the structural architecture of Múlajökull and the impact of its latest surge on the glacier surface.The mapping reveals that Múlajökull comprises a rapidly flowing central section bounded by slower flowing sections on either side. The boundary between these sections is marked by a series of poorly to well-developed brittle shear zones characterized by sigmoidal, en-échelon tension fissures, which can be used to establish the sense of shear within the ice. Analysis of these brittle deformation structures reveals a flow pattern of the Múlajökull margin that can be linked to a complex interplay between subglacial topography and glacier flow. The subglacial topography is characterized by an overdeepening that is delimited by an arcuate ridge near the present (2015) ice margin, and a series of elongate streamlined bedforms (drumlins) in the ice-marginal zone. A study of sedimentary ridges immediately in front of the present glacier margin shows that they are mainly composed of massive diamiction containing blocky clasts and localized pockets of sorted sediments. The distribution and orientation of these ridges has been correlated with the fracture pattern on the surface of Múlajökull. This indicates that the majority of these ridges formed through the squeezing up of mobile sub-glacial sediments(till) into open longitudinal fractures. Transverse ridges most likely represent seasonal, small push moraines. The study widens the understanding of structural flow dynamics in surging piedmont glaciers and the landform assemblage associated with these glaciers. The relationship between ice surface structures and landforms exposed upon ice retreat is ...